Radiation Safety and Future Innovative Diagnostic Modalities. (21st May 2008) - Radmayr, Christian
Abstract : One must demand an accurate, safe, radiation-free, and noninvasive method for reflux examination as the ideal possibility for reflux screening. Of course the available different imaging modalities are far from this ideal situation, but minimal radiation exposure is indeed a permanent objective. Additionally since all of these studies might be quite stressful to the child and the family, a specially designed and equipped environment is obligatory for the comfort of all involved. An absolute ideal modality in the diagnosis of VUR would be the definition of a certain marker in serum or urine that could identify children with VUR without the need for any interventional screening modality. Therefore more and more efforts have to be made in the future to investigate different markers for this purpose. Since reflux is one of the most frequent congenital conditions pediatric urologist have to deal with potential risks that might lead to renal insufficiency, noninvasive and radiation-free modalities should become the methods of choice, hopefully in the near future.